Myeloid cell‐specific topoisomerase 1 inhibition using DNA origami mitigates neuroinflammation. (20th May 2022) - Zhu, Keying; Wang, Yang; Sarlus, Heela; Geng, Keyi; Nutma, Erik; Sun, Jingxian; Kung, Shin‐Yu; Bay, Cindy; Han, Jinming; Min, Jin‐Hong; Benito‐Cuesta, Irene; Lund, Harald; et al.
Abstract: Targeting myeloid cells, especially microglia, for the treatment of neuroinflammatory diseases such as multiple sclerosis (MS), is underappreciated. Our in silico drug screening reveals topoisomerase 1 (TOP1) inhibitors as promising drug candidates for microglial modulation. We show that TOP1 is highly expressed in neuroinflammatory conditions, and TOP1 inhibition using camptothecin (CPT) and its FDA‐approved analog topotecan (TPT) reduces inflammatory responses in microglia/macrophages and ameliorates neuroinflammation in vivo . Transcriptomic analyses of sorted microglia from LPS‐challenged mice reveal an altered transcriptional phenotype following TPT treatment. To target myeloid cells, we design a nanosystem using β‐glucan‐coated DNA origami (MyloGami) loaded with TPT (TopoGami). MyloGami shows enhanced specificity to myeloid cells while preventing the degradation of the DNA origami scaffold. Myeloid‐specific TOP1 inhibition using TopoGami significantly suppresses the inflammatory response in microglia and mitigates MS‐like disease progression. Our findings suggest that TOP1 inhibition in myeloid cells represents a therapeutic strategy for neuroinflammatory diseases and that the myeloid‐specific nanosystems we designed may also benefit the treatment of other diseases with dysfunctional myeloid cells. Synopsis: Topoisomerase 1 is upregulated in activated microglia, suggesting a potential therapeutic target in neuroinflammation. Myeloid‐specific delivery of the TOP1 inhibitor topotecan using a novel nanosystem reduces neuroinflammation and ameliorates multiple sclerosis‐like disease progression. Connectivity map‐based drug screening reveals potential microglia modulating drugs including TOP1 inhibitors. TOP1 is involved in microglia activation and neuroinflammation and represents a therapeutic target. A DNA origami‐based drug delivery system (MyloGami) is developed for targeting myeloid cells. Myeloid cell‐specific TOP1 inhibition (TopoGami) mitigates experimental autoimmune encephalomyelitis. Abstract : Topoisomerase 1 is upregulated in activated microglia, suggesting a potential therapeutic target in neuroinflammation. Myeloid‐specific delivery of the TOP1 inhibitor topotecan using a novel nanosystem reduces neuroinflammation and ameliorates multiple sclerosis‐like disease progression.